2016
DOI: 10.1177/1078345816670161
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Adversity and Mental Health Correlates of Obesity in a Population at Risk

Abstract: The staggering prevalence of obesity and obesity-related health conditions takes exorbitant tolls on health care resources. This cross-sectional study with private evaluations of 636 adult inmates in a southern state prison was conducted with regressions comparing obese (body mass index [BMI] ≥ 30) to nonobese individuals to define obesity risk factors. Obese individuals more likely were female, were victims of childhood sexual abuse, suffered greater severity of childhood sexual abuse, attempted suicide, repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 64 publications
(88 reference statements)
0
9
3
Order By: Relevance
“…Further research, probably with larger sample sizes should explore the possible relationship between low blood pressure and suicidal behaviour. Unlike some previous research findings, 7 , 8 , 9 , 14 , 15 , 16 , 22 , 23 , 24 this investigation did not show a significant association between diabetes, raised TC, overweight or obesity, inadequate physical activity, sedentary behaviour, insufficient fruit and vegetable intake and suicidal behaviour.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Further research, probably with larger sample sizes should explore the possible relationship between low blood pressure and suicidal behaviour. Unlike some previous research findings, 7 , 8 , 9 , 14 , 15 , 16 , 22 , 23 , 24 this investigation did not show a significant association between diabetes, raised TC, overweight or obesity, inadequate physical activity, sedentary behaviour, insufficient fruit and vegetable intake and suicidal behaviour.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, health risk behaviours were found to be associated with suicidal behaviour, including inadequate physical activity and high sedentary behaviour, 14 , 15 , 16 substance use (alcohol, tobacco and drugs), 17 , 18 , 19 passive smoking, 20 , 21 poor dietary behaviour, such as inadequate fruit and vegetable intake, 22 and overweight or obesity. 23 , 24 …”
Section: Introductionmentioning
confidence: 99%
“…Although causal relationships cannot be determined here, the potential benefits and relative low risk/cost of resilience interventions suggest strong reasons for prospective studies testing such interventions among people with schizophrenia (with or without a history of childhood trauma) on physical health outcomes, especially metabolic effects. 1, 2…”
Section: Discussionmentioning
confidence: 99%
“…Childhood maltreatment has been linked to worse mental and physical health and premature mortality in the general population. 14 Afifi et al reported that all types of childhood abuse were associated with physical illnesses, increased risk of obesity, and worse self-reported physical health in a nationwide Canadian study. 5 Even when accounting for sociodemographic variables, smoking and obesity, abuse was associated with a variety of physical illnesses including arthritis, cancer, stroke and back problems.…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation in previous studies was assessing the association between acculturation and obesity among immigrant children by only controlling for basic demographic characteristics and food intake. 33 34 However, other factors, such as the number of children in a family, 35 mental health 36–38 and the environmental, socioeconomic, cultural and behavioural difference between sending and receiving communities 39 were also related to acculturation and obesity and should be considered as confounding factors. For instance, previous studies showed that social anxiety had complex relationships with acculturation 38 and it was associated with high BMI.…”
Section: Introductionmentioning
confidence: 99%